1927
DOI: 10.1056/nejm192703101961001
|View full text |Cite
|
Sign up to set email alerts
|

Obscure Lesions of the Shoulder; Rupture of the Supraspinatus Tendon

Abstract: The chief point of this paper is to advocate early exploratory incision in cases of severe shoulder injuries with negative X-Rays.T wish I had the best of reasons for defending this position-namely that I had repeatedly done what I advise and been glad that I had. As a matter of fact I have never done an exploratory operation on an early case of injury to the shoulder nor do I remember ever having the opportunity. Nor am I likely to see such cases in the future, for I have no connection with any clinic which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
206
0
8

Year Published

1939
1939
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(252 citation statements)
references
References 0 publications
8
206
0
8
Order By: Relevance
“…The arm is very mobile via the connection to the scapula and its joint structure (a small saucer within a large cup). This mobility goes at the expense of the stability of the joint 21 and makes it especially vulnerable for the development of instability complaints. 22 In the current study, we looked at the development of musculoskeletal pain during and after the rehabilitation process and found that pain complaints develop very quickly, which leads to the conclusion that pain was not simply due to overuse.…”
Section: Discussionmentioning
confidence: 99%
“…The arm is very mobile via the connection to the scapula and its joint structure (a small saucer within a large cup). This mobility goes at the expense of the stability of the joint 21 and makes it especially vulnerable for the development of instability complaints. 22 In the current study, we looked at the development of musculoskeletal pain during and after the rehabilitation process and found that pain complaints develop very quickly, which leads to the conclusion that pain was not simply due to overuse.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention consisted of the Codman exercise [4], shoulder wheel exercises [6], self-stretching exercises [6], wall-ladder exercises [6,16], and self-stretching exercises (for improving abduction, flexion, external rotation, internal rotation, and horizontal adduction).…”
Section: Common Supervised Exercisesmentioning
confidence: 99%
“…This condition was first described by Duplay [3] who called it "periarthrite scapulo-humerale." Codman [4] first introduced the term "frozen shoulder" and described it as a "class of cases which are difficult to define, difficult to treat and difficult to explain from the point of view of pathology" [5]. Neviaser [5] called it adhesive capsulitis, as he, under arthroscopy, observed that the capsule looked thickened and adhered to underlying bone and could be peeled off from the bone.…”
Section: Introductionmentioning
confidence: 99%
“…In the post-calcification stage, calcium is resorbed and the area is remodelled [19,26]. Based on the pathogenesis of histic hypoxia, the hypoxic state produces a lack of irrigation of the 'critical area' near the insertion of the supraspinatus tendon and induces calcified deposits [27,28].…”
Section: Discussionmentioning
confidence: 99%